Disaster Risk Reduction and Management of the Province of Siquijor: A Basis for a Strategic Development Plan - Zerna, Enrico (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to determine the extent of implementing the Disaster Risk Reduction and Management Program (DRRMP) in the province of Siquijor and its impact on the communities that are victims of hazards. The study employed a descriptive-correlational research method using a standardized questionnaire. It was conducted with a sample size of 60 DRRM council members and 300 randomly picked community members. The statistical tools used are mean, Pearson Product-Moment Correlation Coefficient, Kruskal-Wallis H-test, and t-test. Necessary protocols stipulated by the Ethics Committee of Foundation University were strictly followed. The salient findings are as follows: DRRM council rated the implementation of the DRRMP as Very High, while community members assessed the implementation as High; the result underscored notable discrepancies between the two assessments as the community members disclosed some inadequacies in implementing the program. They revealed their sentiments by giving a lower rating compared to that of the council members' assessment, particularly in disaster preparedness, disaster response, and disaster recovery and rehabilitation; the extent of DRRMP's impact on the victims is High; no significant relationship exists between the importance of the DRRMP implementation and its effects on the victims of hazards; and DRRM council members' age, experience, and training cannot account for the differences in the extent of DRRMP implementation. Consequently, it was concluded that if every local government unit prioritizes these inadequacies of the program and implements it effectively, the country will be better prepared for any upcoming challenges. Thus, a strategic development plan is recommended for implementation.